Estudo e modelagem da transferência de potência sem fios para múltiplos receptores - Souza, Wanberton Gabriel de (2020)
The use of electric energy is present in countless activities of our daily life. Most of these activities require some mobility. But the use of cables in the transmission of electricity limits these activities. Today, we have a series of autonomous electrical devices or equipment that, despite the portability of these devices, their mobility is subject to load replacement. Also, in medicine, several internal implants that require small batteries, requiring periodic replacement, through surgical procedures that could be avoided if it was possible to recharge. These limitations drive the development of wireless energy transmission technology. Therefore, this work aims at the mathematical modeling of a wireless energy transmission system with multiple receivers and to investigate numerically and experimentally the efficiency of this system. For this purpose, the influence of the variation of the physical parameters of the project is theoretically investigated, such as the number of turns and the type of coil of the emitter / receiver’s system, relative positioning between the emitter and receivers beyond the separation distance. Experimental results are presented with the coils and the prototype built, for several configurations of receivers, in order to demonstrate the validity of the developed model the points of maximum power transfer (MPT), according to the numerical analysis.